PROFIL KESALAHAN SISWA KELAS VII SMP NEGERI 1 DAKO PEMEAN DALAM MENYELESAIKAN SOAL OPERASI HITUNG BILANG BULAT DITINJAU DARI KEMAMPUAN MATEMATIKA : The Profile Of Errors In Grade VII Students AT SMP NEGERI 1 DAKO PEMEAN In Solving Problems On Arithmetic Operations Of Integers Reviewed Mathematical Ability - Putri, Cindy Ade; Paloloang, Baharuddin; Pathuddin, Pathuddin; Murdiana, I Nyoman (Universitas Tadulako, 2024)
This study aims to obtain a description of conceptual and procedural the error profiles by seventh grade students of SMP Negeri 1 Dako Pemean in solving integers arithmetic operation problems in terms of mathematical ability. The subjects of this study were students of class VII B SMP Negeri 1 Dako Pemean in the 2023/2024 school year. There are 3 students, 1 student who has low math ability, 1 student who has moderate math ability, and 1 student who has high math ability. The subjects in this study were selected based on the average mathematics score of the students' Midterm Examination (UTS) results and recommendations from the mathematics teacher. This research used a qualitative approach with descriptive research type. Data collection was carried out by means of observation, written tests, and interviews. The results of the study were analyzed based on several steps, data condensation, data presentation, conclusion drawing. The results showed that: 1) the error profile of high mathematics ability students made conceptual errors and procedural errors. Subjects with high mathematical ability made mistakes in solving integer arithmetic operation problems even though they understood the concepts of addition, subtraction, multiplication, or division in integers. 2) The error profile of students with moderate mathematics ability made conceptual errors and also procedural errors. Subjects with moderate math ability did not understand the concept of arithmetic operations on negative integers, subjects with moderate math ability only understood operations on positive numbers. 3). the error profile of low mathematics ability students also made conceptual errors and procedural errors. Subjects with low mathematics ability made more errors, errors in the solution steps, calculation operation errors in the addition of numbers with the same negative sign so that they were wrong in determining the results of the calculation operation, and also made calculation errors in adding large numbers, calculation errors in division and also in multiplication of integers.